Use of Comparative Symbols Based on Data Type to Formulate a Questionnaire - Faizal, Mochammad; Hidayatullah, Mochammad Rizky; Putra, Aulia Kharisma (Future Science, 2020)
When it comes to using the unit of a number, some researchers cannot distinguish when to use the comparison symbol while designing a questionnaire. This study will discuss how the use of comparative symbols by the type of data in the questionnaire questions through literature studies. It can be concluded that the use of comparison symbols in the questionnaire options cannot be done when the nominal data type is used. The results of this study can be implemented for designing a research instrument that uses a comparison symbol on the question options.